Immunomodulator Activity Test of Curucuminoid Extract Derived from Turmeric Rhizome (Curcuma domestica Val.) In VCO On Rats Injected with Staphylococcus aureus Against an Increase in The Concentration of Leucocyte and Its Components. - Pratiwi, Indah; Yuandani; Putra, Effendy De Lux; Satria, Denny (International Journal of Science, Technology & Management, 2023)
One of the medicinal Zingiberaceae plants which is regularly used by the society as a traditional remedy is turmeric rhizome. The pharmacological properties of turmeric rhizome include anti-inflammatory, anti-immunodeficiency, anti-viral. Anti-bacterial, anti-fungal, anti-oxidant, anti-carcinogenic, and anti-infectious. This study aimed to identify the immunomodulator activity of curcuminoid extract of turmeric rhizome against the increase of leucocyte and its components, lymphocyte and neutrophil in white Galur Wistar rats that had been injected with Staphylococcus aureus. These test animals were given curcuminoid extract in VCO 100 mg/ml on a dosage of 1 ml, 0,5 ml, 0,25 ml curcuminoid powder 200 mg/kg body weight. Curcuminoid was suspended in Na CMC0,5%, Levamisole 25 mg/kg of body weight suspended in Na CMC 0,5%, VCO 1 ml. For the negative control, merely Na CMC 0,5% was given. The extract was orally given daily for 14 days. On the 4th day, Staphylococcus aureus was injected intra-peritoneally. The rats’ blood was then drawn from the heart and was observed to calculate the volume of the leucocytes, lymphocyte, and neutrophil which was conducted using flow cytometry.The findings suggested that there was a significant difference between the immunomodulatory activity of the curcuminoid extract in VCO at the doses of 1 ml, 0,5 ml, 0,25 ml on the increase in leucocyte, lymphocyte, and neutrophil compared to that of the negative control.Therefore, the findings of this study indicated that the extracts of curcuminoid in VCO could increase the number of leucocytes, lymphocytes, and neutrophils. Thus, the curcuminoid extract of turmeric rhizome in VCO potentially possessed immunomodulatory activity.